Danos de Rhopalosiphum padi (Linnaeus, 1758) (Hemiptera : Aphididae) em cultivares e estádios fenológicos de trigo - Savaris, Marcoandre (2010)
The increase of Rhopalosiphum padi populations in wheat crops in recent years has caused considerable damage, causing demand for knowledge about the potential damage of this pest in this culture. Three experiments were conducted in greenhouse (completely randomized) aiming of characterize the damage of R. padi in different growth stages of wheat cultivars. In experiments I (tillering) and II (elongation) the treatments were: cultivars (BRS Guabiju, BRS Timbaúva and Embrapa 16) and infestation levels (0 and 40 aphids/plant). In experiment III (BRS Guabiju - tillering) the treatments were duration (6, 14 and 20 days) and infestation levels (0, 10 and 40 aphids/plant) with and without elimination of the offspring. After the infestation period the following evaluations were performed: yellowing and height of plants; number of tillers, ears and grains; grain yield; thousand grains weight; hectoliter weight; dry mass of shoots and roots and germination and vigour tests. In experiments I and II the cultivar BRS Timbaúva had the lowest reduction in the parameters evaluated and the lowest rates in populational growth of R. padi when compared to cultivars BRS Guabiju and Embrapa 16. In experiment III the parameters evaluated indicated that the percentage of loss was increasing gradually as the number of aphids/day increased. In conclusion, the duration, in days, and the infestation levels of R. padi in the cultivars are directly proportional to the severity of the damage, although each genotype evaluated demonstrated a different response to the attack of R. padi